Manajemen Penanaman Nilai-Nilai Spiritual dalam Meningkatkan Karakter Santri Di Dayah Terpadu Ulumul Islam Kecamatan Tanah Jambo Aye - Kausar; M. Daud, Al Husaini; hayati, Nur (Pase: Journal of Contemporary Islamic Education, 2022)
: Management is very important in forming quality spiritual values, so that an Islamic educational institution does not only focus on achievement, but focuses on expressing spiritual values ​​and achievements. The inculcation of spiritual values ​​is very important for santri today through cultivating, setting an example and habituating these values ​​to santri, thus forming the inculcation of spiritual values ​​and imparting knowledge that will be applied in the dayah, family and community environment. Santri education at Ulumul Islam Integrated Dayah, Tanah Jambo Aye District combines an integrated learning curriculum, which forms students to have strong and sturdy knowledge, skills, and spiritual values. The formulation of the problem is: (1). What is the plan for instilling spiritual values ​​in improving the character of students in the Dayah Terpadu Ulumul Islam, Tanah Jambo Aye District? (2). How is the implementation of instilling spiritual values ​​in improving the character of students in the Ulumul Islam Integrated Dayah, Tanah Jambo Aye District? (3). How to evaluate the inculcation of spiritual values ​​in improving the character of students in the Ulumul Islam Integrated Dayah, Tanah Jambo Aye District? (4). How effective is the inculcation of spiritual values ​​in improving the character of students in the Dayah Terpadu Ulumul Islam, Tanah Jambo Aye District? The research method used is a qualitative method with a descriptive approach. Data collection techniques are in the form of observation, interviews and documentation. The results of the research show that the spiritual values ​​instilled in students are in the form of obedience, trustworthiness, sincerity, responsibility, discipline, independence, honesty, respect, courtesy, affection, caring, cooperation, humility and forgiveness and management of instilling spiritual values ​​in improving the character of students in Dayah Terpadu Ulumul Islam District. Tanah Jambo Aye, has a programmatic plan for instilling spiritual values ​​through deliberations of the father's leadership, the teacher's council, the guidance of the santri. The implementation of the program for instilling spiritual values ​​in students is in accordance with the planning and supervision activities of the foundation, Islamic school leaders, teacher councils and santri coaches. Conducting a thorough evaluation of the evaluation system, constraints and follow-up plans, and the effectiveness of instilling spiritual values ​​can be concluded effectively, because the father's leadership has been able to carry out its role and function as the father's leader, both the position of teachers, managers, administrators, supervisors, and innovators, as well as the suitability between implementation and the goals that have been set.